METHOD OF MULTI-OBJECTIVE RESOLUTION OF TWO-AIRCRAFT CONFLICT IN THREE-DIMENSIONAL SPACE BASED ON DYNAMIC PROGRAMMING - Vasyliev, Denys (Proceedings of National Aviation University (archive), 2016)
Purpose: Current global trends of air traffic growth cause the increasing of number of aircraft conflicts. The actual problem is a development of new methods for conflict resolution that should provide the synthesis of conflict-free trajectories in three-dimensional space according to different flight efficiency criteria. Methods: The problem of multi-objective resolution of potential conflict between two aircraft in three-dimensional space is considered. The method of multi-objective resolution of conflict between two aircraft using heading, speed and altitude change maneuvers has been developed. Described method provides the synthesis of conflict-free flight trajectory according to criteria of flight regularity, flight economy and the complexity of maneuvering based on dynamic programming. The continuous-time and discrete-time equations of multi-objective dynamic programming for determining the set of Pareto-optimal estimations of conflict-flight trajectories are shown. The synthesis of Pareto-optimal trajectories is carried out using the forward procedure of discrete multi-objective dynamic programming. The simulation of flight trajectories is performed using the special model of controlled aircraft motion. The selection of optimal conflict-free trajectory from the set of Pareto-optimal trajectories is carried out using the convolution of optimality criteria. Within described method, the following procedures have been defined: for prediction of separation minima violations; for aircraft states and controls discretization; for interpolation of trajectories efficiency estimations according to defined optimality criteria. Results: The analysis of the proposed method is performed using computer simulation which results show that computed optimal conflict-free trajectory ensures the conflict avoidance and complies with defined optimality criteria. Discussion: The main advantages of the method are: heading, speed and altitude change maneuvers are used for conflict avoidance; the multi-objective optimization of conflict-free trajectories is applied; the using of dynamic programming enhances the computational efficiency. Proposed method can be used for development of advanced conflict resolution tools for automated air traffic control systems.